(untitled) (Northern International Medical College Journal, 2018)
Background : Dengue is a mosquito-borne (Ades Agepti) infection which in recent years has become a major public health problem. It is now endemic in more than 100 countries in Africa, America, Eastern Mediterranean, South-East Asia and Western Pacific areas. According to WHO currently approximately 50 million cases of dengue fever occur every year. Objective : To evaluate the current clinical picture, outcome and serology of children suffering from dengue fever admitted in a tertiary care children hospital. Methodology : It is a hospital based prospective observational study carried out among the children having Dengue infection admitted during the period of June to December 2016 in Dhaka Shishu (Children) Hospital. After obtaining informed consent 78 suspected cases of dengue fever patients were enrolled for this study. Patient with any identified specific infection or febrile illness more than 14 days and serologically dengue negative cases were excluded from the study. A detailed history, demographic variables, clinical examination and relevant laboratory investigations were assessed. The data were collected in a predesigned structured questionnaire and were analyzedwith the help of SPSS-21. Result : Out of 78 suspected dengue cases a total of 56 cases were serologically dengue positive. Therefore 22 serologically dengue negative cases were excluded. Most common presenting symptoms were fever (100%) followed by myalgia76.79%, retro-orbital pain73.21%, and conjunctival hemorrhage 55.35%, skin rash 55.35%, with other symptoms constituting the rest. Among the serologically positive dengue cases those who presented with fever for 3 days or of lesser duration, NS1 Ag was positive in 34 cases ( 43.58%) and those who presented with fever for 6 days or more, 14 cases (17.95%) were dengue IgM positive and 8 cases (10.25%) were dengue IgG positive with accompanying low level IgM positive; platelet count 94333/mm3 (±68330), PCV 35 (±3.95) and SGPT 210 U/L(±80).Among 56 dengue positive cases 31(55.4%) were male and 25 (44.6%) were female, The age range was 1 years to 18 years with mean 6.66 ±3.69, predominant age group was 6 years to 12 years. Final diagnosis according to WHO classification were DF 42.68%, DHF-l 32.14%, DHF–ll 16.07%,DHF-lll 8.93%. Outcome of the disease were 89.3% discharge with advice (DA),7.1% discharge on request(DOR), 3.6% left against medical advice(LAMA) and no death. Conclusion : The trend of Dengue infection in Bangladesh has been changing very rapidly. In this study our observation was incidence of dengue was more in male child, peak age group being 6 years to 12 years with most admissions during the month of September. Fever with pain (body ache, retro orbital pain), headache and maculopapular rash, positive NS1Ag and dengue IgM were the main findings found in children with dengue. Most of the dengue cases were DF and DHF-l in our study. Northern International Medical College Journal Vol.9(1) July 2017: 274-277